Nursing and work with a children groups: an integrative review (Research, Society and Development, 2020)
Objective: To analyze publications developed by nurses regarding child groups. Methodology: This is an integrative review, carried out between February and March 2019, in the Virtual Healht Library – BIREME. Results and Discussion: Ten articles were analyzed, allowing the identification of two categories: Characterization of the types of groups used and your importance in the activities of nurses and The use of ludic and the Therapeutic Toy in the group activity as a strategy to promote integral care. Discussion: Most articles on nurses’ production about groups with children use a qualitative approach and the groups appear as a path for intervention in the clinical practice of child care and as well as a methodological strategy of research. Final Considerations: Nursing needs more incentive to perform this type of intervention since this research presents promising results in the implementation of this practice, that allows improving the nursing care as a whole.